Corn Business Development Opportunities Through an Agribusiness Approach - Nuraeni; Rasmeidah Rasyid Patingari; Nurfitriana Alifia (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2021)
The purpose of this study is to (1) examine the application of the corn farming agribusiness system, (2) examine the production and income generated by corn farming, (3) examine the feasibility of corn farming, and (4) examine the prospects for corn farming development. Tanah Towa Village is located in Kajang District, Bulukumba Regency, South Sulawesi. Simple random sampling was used to select up to 59 respondents. The descriptive statistical analysis, farm income analysis, farming feasibility analysis, and time series analysis were all used to analyze the data. The results indicated that (1) the application of the agribusiness farming system with the production facilities subsystem met the correct criteria in 68% of cases and was incorrect in 32% of cases. (2) the average farm production of corn in Tanah Towa Village, Kajang District, Bulukumba Regency in the form of dry shells is still low at 2,204.4 kg/ha, compared to the subdistrict level of 3,733 kg/ha, with farmer income of Rp. 5,942,319/ha. (3) The feasibility of corn farming has increased (R/C = 3), indicating that it is feasible to develop; (4) The prospect of developing corn production in Kajang District has increased, indicating that it has favorable development prospects.significantly, to the point where it now has favorable development prospects.